2020
DOI: 10.3390/ma13225190
|View full text |Cite
|
Sign up to set email alerts
|

On the Surface Residual Stress Measurement in Magnesium Alloys Using X-Ray Diffraction

Abstract: X-ray penetration in magnesium alloys is significant due to the low X-ray mass attenuation coefficient. To measure the surface residual stresses in magnesium alloys, a correction needs to be made to account for penetration depth. The residual stresses in as-received and shot peened AZ31B-H24 rolled sheet samples were measured using two-dimensional X-ray diffraction (2D-XRD) method. The electro-polishing layer removal method was used to find the residual stress pattern at the surface and through the depth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…70 Thus, the HVAF-sprayed HA coating retained compressive residual stress due to high velocity and impact with a low temperature of in-flight particles, which is considered beneficial in nature. Also, the presence of compressive residual stress positively alters mechanical properties 68 and delays crack initiation, leading to a longer life 71 and significantly affecting the tribological performance of the coating by reducing wear debris. 72 Recently, Papanikolaou et al 20 using molecular dynamics simulations, while studying the solidification of aluminum, revealed that the residual stress and crystallinity of the material are inter-related to each other.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…70 Thus, the HVAF-sprayed HA coating retained compressive residual stress due to high velocity and impact with a low temperature of in-flight particles, which is considered beneficial in nature. Also, the presence of compressive residual stress positively alters mechanical properties 68 and delays crack initiation, leading to a longer life 71 and significantly affecting the tribological performance of the coating by reducing wear debris. 72 Recently, Papanikolaou et al 20 using molecular dynamics simulations, while studying the solidification of aluminum, revealed that the residual stress and crystallinity of the material are inter-related to each other.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There are two main categories of residual stress measurement methods: non-destructive and destructive techniques. These include X-ray diffraction [7,8], neutron diffraction [9,10], layer removal methods [11,12], and the incremental hole-drilling method [13][14][15], among others. Each method has its applicability and limitations.…”
Section: Introductionmentioning
confidence: 99%